Examination of the recitations to Ali in Al-Tabarsi commentary - Saylan, NesriŞah (Gazi Universitesi, Turk Kulturu ve Haci Bektas Veli, 2018)
The aim of this study is to examine the recitations relating to Al? in al-Tabars?, one of the Shiî commentators, in his work Majmau'l-Bay?n f? Tafs?r al-Qur'?n and the role of those recitations in terms of language and meaning. Al? who grew up in the education of the Messenger from the very early age has an important place in the science of religion as in many branches of science. He learned the Qur?n from the Messenger himself and became one of the hafiz companions by memorizing Qur?n in Hz Muhammed's era. Al? who educated famous scholars like Abu'l-Asvad al-Dual?, Ab? Abd al-Rahm?n b. Ab? Layl? and Ab? Abd al-Rahm?n al-Sulam? in the science of the Qur?n recitation was considered in biographical sources as among the readers of the Qur'an. Al? took place in the sanads of seven imams and ten imams of Qur?nic recitation. As a matter of fact, Al? appeared in the chains of sanads of the seven imams of Qur?nic recitation Ab? Amr b. Al?, Asım b. Bahdala and Hamza b. Hab?b; and the ten imams of Y?k?b al-Hadram?. The recitations relating to Al? were mentioned in many commentary sources from very early times up to now, which were referred to the contribution for the interpretation of the verse. al-Tabars? who is one of the Sh?'? commentators described the recitation referring to Al? in his interpretation and made use of these recitations in comentary and te'vil efficietly. In this context, the aim of the article, in the example of Al?'s recitation, is to examine the transferring method and process of recitations in al-Tabars?'s interpretation and their impact on the recitation as exceptional readings (Sh?dhdh) and truth readings. © 2018 Gazi Universitesi, Turk Kulturu ve Haci Bektas Veli. All rights reserved.
Tabersi tefsirinde Hz. Ali'ye nisbet edilen kiraatlerin incelenmesi
Keywords: Al-Tabars?; Al?; Recitation; Sh?dhdh; Sh?'a; Tafs?r; Variant readings